Motivation: A Supporting Factor of the Success in Second Language Acquisition - V. Luluk Prijambodo (Widya Mandala Surabaya Catholic University, 2012)
Motivation in second language acquisition is one of the influencing factors that determine the success or failure in mastering the language being studied. Since motivation is personal in nature and its intensity is relative, it needs to be kept constant and then promoted. The teachers in the classroom setting, besides the students themselves, play important roles in maintaining and promoting the intensity of motivation. In order to be able to keep constant and increase the intensity of motivation, the nature of motivation is necessary to be understood in depth.